Comparison of the Effectiveness of Emotion-Focused Therapy and the Existential–Spiritual Reconstruction Protocol in Enhancing Quality of Life Among Women Attending Healthcare Centers in Bushehr City - Barani, Azam; Gholamzadeh Jofreh, Maryam; Kazemian Moghadam, Kabra (Psychology of Woman Journal, 2026)
Objective: The present study aimed to compare the effectiveness of Emotion-Focused Therapy (EFT) and the Existential–Spiritual Reconstruction Protocol in improving the quality of life among women attending healthcare centers in Bushehr City.Methods and Materials: This study employed a quasi-experimental design with a pretest–posttest and a control group. The statistical population consisted of women with a history of miscarriage who attended healthcare centers in Bushehr City. From the eligible participants, 45 individuals were selected and randomly assigned to three groups of 15 participants each (two experimental groups and one control group). Initially, a pretest was administered to all three groups. Subsequently, the two experimental groups received therapeutic interventions over eight 90-minute sessions, and finally, a posttest was conducted for all groups. Data were collected using the Quality of Life Questionnaire (SF-36). The data were analyzed using SPSS software, version 25.Findings: The results indicated a significant difference between the effectiveness of the miscarriage-related Existential–Spiritual Reconstruction Protocol and Emotion-Focused Therapy in improving the quality of life of women with a history of miscarriage. In most dimensions of quality of life, both experimental groups (ESR-A and EFT) showed significant differences compared to the control group (p < .05). Therefore, both interventions led to improvements in quality of life dimensions compared to no intervention. Furthermore, direct comparison between the two experimental groups revealed that in some dimensions, the level of improvement in the first experimental group (ESR-A) was greater than that in the second experimental group (EFT).Conclusion: The findings of this study demonstrated that both interventions are effective in improving the quality of life of women with a history of miscarriage; however, the Existential–Spiritual Reconstruction Protocol, which is developed based on qualitative findings and tailored to the cultural context of the community, showed greater effectiveness.